Multicenter Validation of Association Between Decline in MRI‐PDFF and Histologic Response in NASH. Issue 4 (9th October 2020) - Loomba, Rohit; Neuschwander‐Tetri, Brent A; Sanyal, Arun; Chalasani, Naga; Diehl, Anna Mae; Terrault, Norah; Kowdley, Kris; Dasarathy, Srinivasan; Kleiner, David; Behling, Cynthia; Lavine, Joel; Van Natta, Mark; et al.
Abstract : Background and Aims: Emerging data from a single‐center study suggests that a 30% relative reduction in liver fat content as assessed by magnetic resonance imaging–proton density fat fraction (MRI‐PDFF) from baseline may be associated with histologic improvement in nonalcoholic steatohepatitis (NASH). There are limited multicenter data comparing an active drug versus placebo on the association between the quantity of liver fat reduction assessed by MRI‐PDFF and histologic response in NASH. This study aims to examine the association between 30% relative reduction in MRI‐PDFF and histologic response in obeticholic acid (OCA) versus placebo‐treated patients in the FLINT (farnesoid X receptor ligand obeticholic acid in NASH trial). Approach and Results: This is a secondary analysis of the FLINT trial including 78 patients with MRI‐PDFF measured before and after treatment along with paired liver histology assessment. Histologic response was defined as a 2‐point improvement in nonalcoholic fatty liver disease activity score without worsening of fibrosis. OCA (25 mg orally once daily) was better than placebo in improving MRI‐PDFF by an absolute difference of −3.4% (95% confidence interval [CI], −6.5 to −0.2%, P value = 0.04) and relative difference of −17% (95% CI, −34 to 0%, P value = 0.05). The optimal cutoff point for relative decline in MRI‐PDFF for histologic response was 30% (using Youden's index). The rate of histologic response in those who achieved less than 30% decline in MRI‐PDFF versus those who achieved a 30% or greater decline in MRI‐PDFF ( MRI‐PDFF responders ) relative to baseline was 19% versus 50%, respectively. Compared with MRI‐PDFF nonresponders, MRI‐PDFF responders demonstrated both a statistically and clinically significant higher odds 4.86 (95% CI, 1.4‐12.8, P value < 0.009) of histologic response, including significant improvements in both steatosis and ballooning. Conclusion: OCA was better than placebo in reducing liver fat. This multicenter trial provides data regarding the association between 30% decline in MRI‐PDFF relative to baseline and histologic response in NASH.